HuoXueTongFu Formula Alleviates Intraperitoneal Adhesion by Regulating Macrophage Polarization and the SOCS/JAK2/STAT/PPAR-γ Signalling Pathway - Zhao, Min; Bian, Yao-Yao; Yang, Li-Li; Chen, Yan-Qi; Wang, Ya-Jie; Ma, Yan-Ting; Pei, Yu-Qiong; Li, Wen-Lin; Zeng, Li (Mediators of Inflammation, 2019)
Intraperitoneal adhesion is a common complication after abdominal surgery, which seriously affects the quality of life of patients. HuoXueTongFu Formula (HXTF) plays an important role in the prevention and treatment of intraperitoneal adhesions. However, the molecular-related mechanisms are still not fully known. In this study, the model of Intrapetitoneal adhesion was established by cecum abrasion and treated with HXTF for one week. RAW264.7 cells were given LPS, IFN-γ, IL-4, HXTF-medicated serum, and PPAR-γ agonist/antagonist, respectively. Histopathology, flow cytometry, ELISA, real-time PCR, and Western blotting were used to further detect the related protein, M1/M2 polarization tendency, and PPAR-γ nuclear translocation. The deposition of collagen fibres reduced in the local area of rats after the operation with HXTF treatment. Similar to IL-4, HXTF induced a tendency for macrophages to polarize toward M2 and promoted peroxisome proliferator-activated receptor-gamma (PPAR-γ) nuclear translocation. Furthermore, the use of HXTF and PPAR-γ agonists downregulated macrophage M1 polarization-related factors IL-1, IL-6, and TNF-alpha and upregulated M2 polarization-related factors IL-4, IL-10, and TGF-beta 1. Meanwhile, the use of HXTF and PPAR-γ agonists downregulated the SOCS3/JAK2/STAT1 pathway and activated the SOCS1/STAT6/PPAR-γ pathway. These results show that HXTF may reduce intraperitoneal adhesion by inducing macrophage M2 polarization and regulating the SOCS/JAK2/STAT/PPAR-γ pathway.